THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS AND INTERNAL CONTROL ON THE QUALITY OF FINANCIAL STATEMENT WITH INTELLECTUAL INTELLIGENCE AS A MODERATING VARIABLE - Jamaluddin Majid, Memen Suwandi, Lince Bulutoding, Sumarlin, Andi Wawo. (International Journal of Research Science and Management, 2020)
Application of internal control system and accounting information system in management of coffee shopis a very important thing. This financial statements must meet the following characteristics : relevant, reliable, comparable, and understandable. The purpose this study: (1) to find out whether the use of accounting information system and internal controls effect the quality of financial statements.(2) to find out whether intelligence quotient moderates the effect of accounting information system and internal controls on the quality of financial statements. The population in this study are all Cofee Shop in The City Of Makassar. The sample in this study is manager or employees of the financial part of the respondents were 12 respondents. The samples were selected by using a purposive sampling method. Data was collected by distributing questionnaires to the respondents directly concerned. Technical analysis of the data used is multiple regression with SPSS 24. The result showed that: (1) the accounting information system has a positive significant effect on the quality of government financial statements and the internal control system has a significant effect on the quality of financial statements.(2)Intelligence quotient is able to moderate the financial information system towards the quality of financial statements. While intelligence quotient variable is not able to moderate internal controls on the quality of financial statements.